Development and evaluation of calcium hydroxide‐coated, pericardium‐based biomembranes for direct pulp capping. Issue 1 (7th December 2018) - Klein‐Júnior, Celso A.; Reston, Eduardo; Plepis, Ana M.; Martins, Virginia C.; Pötter, Isabel C.; Lundy, Fionnuala; Hentschke, Guilherme S.; Hentschke, Vítor S.; Karim, Ikhlas El
Abstract: Aim: The aim of the present study was to develop a bovine pericardium biomembrane (BPB) and to evaluate pulp response in vivo. Methods: A double‐layer bovine BPB/chitosan was manufactured, and the porous chitosan side was coated with calcium hydroxide. The microstructure of the matrices was evaluated with electron microscopy. To test pulp response, cavities were prepared on the occlusal surface of Wistar rats' mandibular left first molars and capped with matrices, followed by appropriate adhesives/composite restorations. The animals were divided into three groups: group 1, calcium hydroxide alone; group 2, BPB without calcium hydroxide; and group 3, BPB coated with calcium hydroxide. Specimens were processed and histologically evaluated at 7, 14, and 30 days, postoperatively. Results: Electron microscopy showed porous chitosan surface and a cohesive calcium hydroxide layer. Histological analysis showed that groups 1 and 3 had mild odontoblast layer disorganization, but normal pulp tissue appearance at 7, 14, and 30 days. At the same time points, group 2 showed a loss of general pulp tissue, pulp necrosis, and periapical abscess in some teeth. Conclusion: Coated bovine pericardium‐based biomembranes resulted in favorable outcomes in cases of pulp exposure after a 30‐day observation period, and might protect against injuries caused by adhesive systems and composites.